New factors wanted: Evidence from a simple specification test - HE, Ai (Institutional Knowledge at Singapore Management University, 2018)
In this paper, we examine the pricing errors (PEs) of three kinds of factor models: a) six well known ones– the CAPM, the Fama-French three-factor model, the Carhart four-factor model, the Fama-French five-factor model, the Hou-Xue-Zhang Q-factor model, and the Stambaugh-Yuan mispricing-factor model; b) principal component factors of sixty-two anomalies; c) extracted statistical factors. We find that there is a systematic PE reversal pattern. A spread portfolio that buys stocks in the bottom PE decile and sells stocks in the top PE decile earns significant abnormal returns across all the models, implying that none of them is adequate in explaining the cross section of stock returns. Moreover, the differences between either the PEs or the PE spread portfolios are virtually zero, implying that current factor models improve little beyond the CAPM at pricing individual stock returns. Of the economic forces, the reversal is partially driven but cannot be fully explained by limits-to-arbitrage, lottery demand, and expectation extrapolation.